PENGEMBANGAN MODEL PEMBELAJARAN MENULIS PUISI MBELING DENGAN MEDIA ICT BERBASIS PRACTICAL REHEARSAL PAIRS PADA MATA KULIAH PEMBELAJARAN APRESIASI PUISI MAHASISWA PBSI UNIVERSITAS PGRI SEMARANG - Ngatmini .; Siti Fatimah; Ririn Ardi (Sasindo, 2014)
Presence in the world of poetry mbeling in Indonesia is still sidelined and notproduced either by the public, especially students of Indonesian literature Indonesianlanguage and literature education.Their poetry in the universe perpuisianmbelingIndonesia still sidelined and not produced either by the Indonesian literary society,especially students Indonesian language and literature education. The study was basedon several issues, namely 1) how the needs of faculty and students in learning to writepoetry during this mbeling, 2) how the product stakeholder responses to the model oflearning to write poetry mbeling generated, 3) how the model of learning to writepoetry mbeling with ICT media based PRP were developed, and 4) how theeffectiveness of the learning model to write poetry mbeling with ICT media.The purpose of this study were 1) finding the needs of faculty and students inlearning to write poetry during this mbeling, 2) produce a model of learning to writepoetry mbeling with ICT-based media PRP developed, 3) to formulate a response to thestakeholder model of learning to write poetry that mbelingproduced, and 4) found arate/level learning model effectiveness mbeling write poetry with ICT mediadevelopment results.Used adaptation of the measures Borg and Gall in the study of thisdevelopment. Based on this research, obtained a model of the development that can beapplied effectively in learning to write poetry mbeling. Students enthusiastically wrotepoetry mbeling on facebook and hand-over commentary by another team mate. Inaddition to the successes, there are also weaknesses in this study, the results of studentwriting is still not as good as a poet who has written poems that have professionalmbeling. It is caused by the lack of exercise and the intensity of writing poetry mbelingonly. Meanwhile, the ability to write poetry mbeling undertaken by students have canbe optimized through a model developedKeywords: models of learning, poetry mbeling, practical rehearsal pairs